2022
DOI: 10.1080/2162402x.2022.2124691
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of first-line treatment in cisplatin-ineligible advanced upper tract urothelial carcinoma patients: a comparison of PD-1 inhibitor and carboplatin plus gemcitabine chemotherapy

Abstract: Although several programmed cell death (PD)-1 inhibitors are approved for the first-line treatment of advanced urothelial carcinoma, their efficacy remains unknown in cisplatin-ineligible patients with upper tract urothelial carcinoma (UTUC) compared with gemcitabine plus carboplatin. Data for patients with UTUC were retrospectively retrieved from the electronic medical records of nine institutions between 2018 and 2021. Patients considered ineligible for cisplatin who received either PD-1 inhibitors (n = 70) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…We previously compared the efficacy and safety of PD-1 inhibitors and carboplatin combined with gemcitabine in the first-line treatment of cisplatin-unfit UTUC patients. 33 Our results support the role of PD-1 inhibitors with comparable survival outcomes, longer DOR, and lower toxicity than carboplatin-gemcitabine for cisplatin-ineligible patients, although PD-1 inhibitors may not surpass cisplatin dominance in the treatment of those eligible patients. In this study, we further explore the effect of ICIs in a second-line setting and provide a full spectrum of efficacy and safety of ICI monotherapy for unresectable or metastatic UTUC as a first-line therapy in cisplatin-ineligible patients or second-line therapy in platinum-refractory patients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We previously compared the efficacy and safety of PD-1 inhibitors and carboplatin combined with gemcitabine in the first-line treatment of cisplatin-unfit UTUC patients. 33 Our results support the role of PD-1 inhibitors with comparable survival outcomes, longer DOR, and lower toxicity than carboplatin-gemcitabine for cisplatin-ineligible patients, although PD-1 inhibitors may not surpass cisplatin dominance in the treatment of those eligible patients. In this study, we further explore the effect of ICIs in a second-line setting and provide a full spectrum of efficacy and safety of ICI monotherapy for unresectable or metastatic UTUC as a first-line therapy in cisplatin-ineligible patients or second-line therapy in platinum-refractory patients.…”
Section: Discussionsupporting
confidence: 71%
“…We previously compared the efficacy and safety of PD‐1 inhibitors and carboplatin combined with gemcitabine in the first‐line treatment of cisplatin‐unfit UTUC patients 33 . Our results support the role of PD‐1 inhibitors with comparable survival outcomes, longer DOR, and lower toxicity than carboplatin‐gemcitabine for cisplatin‐ineligible patients, although PD‐1 inhibitors may not surpass cisplatin dominance in the treatment of those eligible patients.…”
Section: Discussionsupporting
confidence: 53%
“…However, clinical differences may lead to different treatment responses in UTUC and bladder cancer, as UTUC only constituted a minor proportion of these studies. Previously, we reported comparable oncological outcomes between PD-1 inhibitor monotherapy and carboplatin plus gemcitabine in first-line treatment of cisplatin-ineligible UTUC patients ( 22 ). Meanwhile, PD-1 inhibitor monotherapy is associated with lower toxicity ( 22 ).…”
Section: Introductionmentioning
confidence: 80%
“…Previously, we reported comparable oncological outcomes between PD-1 inhibitor monotherapy and carboplatin plus gemcitabine in first-line treatment of cisplatin-ineligible UTUC patients ( 22 ). Meanwhile, PD-1 inhibitor monotherapy is associated with lower toxicity ( 22 ). The efficacy of PD-1 inhibitor monotherapy might correlate with various biomarkers, including PD-L1 expression ( 23 ).…”
Section: Introductionmentioning
confidence: 80%
“…Previous research reported that platinum-based chemotherapy, a conventional treatment, may affect the patient’s immune system ( 21 ). Some clinical trials also found that the combination of PD-1 ( 22 )/PD-L1 ( 23 ) inhibitor with platinum-based chemotherapy would enhance the efficacy and safety of monotherapy. Although the immunogenicity caused by platinum drugs is responsible for the effectiveness of combination therapy, the effect of platinum drugs on the TIME is still unknown, especially in BLCA.…”
Section: Discussionmentioning
confidence: 99%